2020
DOI: 10.1534/g3.120.401059
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Contiguous Genome for the Golden-Fronted Woodpecker (Melanerpes aurifrons) via Hybrid Oxford Nanopore and Short Read Assembly

Abstract: Woodpeckers are found in nearly every part of the world and have been important for studies of biogeography, phylogeography, and macroecology. Woodpecker hybrid zones are often studied to understand the dynamics of introgression between bird species. Notably, woodpeckers are gaining attention for their enriched levels of transposable elements (TEs) relative to most other birds. This enrichment of TEs may have substantial effects on molecular evolution. However, comparative studies of woodpecker genomes are hin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 56 publications
2
5
0
Order By: Relevance
“…While a higher gene group recovery rate would be expected for a highly contiguous assembly, we highlight that these results correspond with studies that have found that greater assembly contiguity often does not result in an increased gene group recovery rate, and if an increase is noted, it is often modest ( Korlach et al 2017 ; Low et al 2019 ). Indeed, we find our recovery rates to be similar to those of the M. aurifrons assembly, with 92.6% of complete BUSCO gene groups recovered from the aves_odb9 dataset ( Wiley and Miller 2020 ). We recovered a high degree of one-to-one synteny with the Chicken Gallus gallus chromosomes, particularly between those of small and medium size ( Figure 1B ).…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…While a higher gene group recovery rate would be expected for a highly contiguous assembly, we highlight that these results correspond with studies that have found that greater assembly contiguity often does not result in an increased gene group recovery rate, and if an increase is noted, it is often modest ( Korlach et al 2017 ; Low et al 2019 ). Indeed, we find our recovery rates to be similar to those of the M. aurifrons assembly, with 92.6% of complete BUSCO gene groups recovered from the aves_odb9 dataset ( Wiley and Miller 2020 ). We recovered a high degree of one-to-one synteny with the Chicken Gallus gallus chromosomes, particularly between those of small and medium size ( Figure 1B ).…”
Section: Resultssupporting
confidence: 64%
“…The final assembly had an L50 of 43.938 Mbp scaffolds and an N50 of 11 ( Figure 1A; Table 1 ). In terms of contiguity (L50 and N50), this assembly represents a ∼3× improvement over a recently published long-read-based Picidae assembly ( Melanerpes aurifrons GCA_011125475.1; Wiley and Miller 2020 ) and represents the first published chromosome-level assembly for Piciformes. BUSCO results also suggested this assembly is of high quality, with modestly high recovery of complete bird-specific and tetrapod-specific gene groups (87.4–91.7%; Table 2 ; Supplementary Files S1–S12).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Complex genomes often result in highly fragmented assemblies ( Koren et al ., 2012 ; Rice & Green, 2019 ). Combining short reads with less accurate long-read sequencing technologies leads to more contiguous genome assemblies ( Austin et al ., 2017 ; Zimin, Puiu, et al ., 2017 ; Zimin, Stevens, et al ., 2017 ; Tan et al ., 2018 ; Dhar et al ., 2019 ; Jiang et al ., 2019 ; Wiley & Miller, 2020 ). On the other hand, the relatively young circular consensus sequencing (CCS) PacBio technology produces reads that are both thousands of bp long and highly accurate.…”
Section: Introductionmentioning
confidence: 99%
“…However, the generation of highquality eukaryotic genomes has been hampered in the past by sequencing costs and assembly complexity, limiting sequenced eukaryotes to those of medical or economical interest (7). More recently, advances in Illumina high-throughput sequencing and emerging long-read sequencing technologies developed by Pacific Biosciences and Oxford Nanopore have also rendered the generation of genome assemblies of large eukaryotes a routine task (8)(9)(10). These proceeding trends in data availability, advanced techniques, and improved affordability require more facilitated access for scientists to analyze these sequence data.…”
Section: Introductionmentioning
confidence: 99%